Radioterapia exclusiva ou combinada com cirurgia e/ou quimioterapia para tumores nasais em cães: revisão sistemática e metanálise - Cruz, Natalia Oyafuso da [UNIFESP] (2018)
Radiotherapy (RT) is a very effective modality in the treatment of solid tumors in animals. This study performed a systematic review of the literature and metaanalysis on the use of ionizing radiation in dogs for malignant nasal tumors and it compared some clinical outcomes among those who used RT alone versus RT associated with surgery and/or chemotherapy (CT). The electronic databases used to search the literature published until January 2018 were MEDLINE, LILACS and SciELO. Clinical studies in dogs, which evaluated the efficacy and safety of RT in several types of tumors, were included. We found 2,732 items regarding search terms. After exclusion by reading the title and the abstract, we selected 157 studies for full reading. Among these, 5 papers corresponded to the question structured by the present study and included in the systematic review. Only 2 articles, related to canine nasal tumor, were included for metaanalysis. The systematic review showed the noninferiority of the RT alone in relation to: mean and median overall survival time (OS), 1 or 2year overall survival rate (OSR), diseasefree interval (DFI) and local recurrence rate (LRR). The metaanalysis demonstrated a favoring RT associated with surgery in terms of local recurrence (p=0.04) and no significant difference in the comparison between RT alone and the association of RT and surgery with 1year OSR (p=0.34). There was a trend favorable to the use of RT alone with 2year OSR (p= 0.05).